#TITLE_ALTERNATIVE# - RACHMAN PRIBADI (NIM : 10208029); Pembimbing : Wahyu Srigutomo, PhD, ARIEF
The shear-wave (S-wave) velocity structure of near surface material hold an important role in geotechnical study. Microtremor survey method has been used to extract S-wave velocity structure information from microtremor records. Assuming the microtremor recordÃ‚Â’s were dominated by surface waves, data analysis and dispersion curve were achieved by using SPAC (Spatial Autocorrelation) analysis method. Thus, least square inversion method is applied to dispersion curve to estimate the shear-wave velocity structure.